2007
DOI: 10.2193/2005-744
|View full text |Cite
|
Sign up to set email alerts
|

Response of Wolves to Experimental Disturbance at Homesites

Abstract: Events during the denning period (parturition to first autumn) often determine the reproductive success of wolves (Canis lupus). Consequently, there is concern about the potential adverse effects of human‐caused disturbance at wolf den and rendezvous sites (homesites), but relatively little information on this subject is available. We conducted standardized experimental disturbance treatments at 12 unique wolf homesites in the Northwest Territories, Canada, during summers 2002 and 2003. The treatment consisted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 10 publications
4
21
0
Order By: Relevance
“…When considering broad targets such as biodiversity, dose-response experiments conducted at the scale of the individual animal lead to well-controlled experiments, but the results are not easily extrapolated to population-level processes, including the persistence of species that are at risk. For example, individuals in natural or captive settings can be exposed to some disturbance stimulus and the fl ight distance, total time of vigilance, or even heart rate can be measured Frame et al 2007 ;Naylor et al 2009 ). Similarly, air and water contaminants can be accurately measured at a point source as units of pollutant (Squires et al 2010 ).…”
Section: Issues Of Scale and Scalingmentioning
confidence: 99%
“…When considering broad targets such as biodiversity, dose-response experiments conducted at the scale of the individual animal lead to well-controlled experiments, but the results are not easily extrapolated to population-level processes, including the persistence of species that are at risk. For example, individuals in natural or captive settings can be exposed to some disturbance stimulus and the fl ight distance, total time of vigilance, or even heart rate can be measured Frame et al 2007 ;Naylor et al 2009 ). Similarly, air and water contaminants can be accurately measured at a point source as units of pollutant (Squires et al 2010 ).…”
Section: Issues Of Scale and Scalingmentioning
confidence: 99%
“…Wolves may be vulnerable to disturbance during the pup-rearing period, when pack movements are restricted by the need to return food to immobile pups at dens (Walton et al, 2001;Frame et al, 2007). Some wolves are tolerant of human activity near their dens (Thiel et al, 1998;Frame et al, 2007), but others move pups to alternative sites in response to disturbance (Chapman, 1977;Ballard et al, 1987;Frame et al, 2007). While Ballard et al (1987) and Frame et al (2007) reported that no mortality occurred at dens where human disturbance caused wolves to move pups, it is possible that such disturbance can reduce reproductive success of wolves.…”
Section: Introductionmentioning
confidence: 99%
“…Some wolves are tolerant of human activity near their dens (Thiel et al, 1998;Frame et al, 2007), but others move pups to alternative sites in response to disturbance (Chapman, 1977;Ballard et al, 1987;Frame et al, 2007). While Ballard et al (1987) and Frame et al (2007) reported that no mortality occurred at dens where human disturbance caused wolves to move pups, it is possible that such disturbance can reduce reproductive success of wolves. However, the relation between industrial development and the reproductive success of wolves has not been studied previously in North America.…”
Section: Introductionmentioning
confidence: 99%
“…Such disturbances may cause permanent movement away from a natal site, territory, or other resource (Ellison and Cleary 1977;Walker et al 2005), abandonment of young by parents (Thomson 1992), or decreased survival of offspring or reproductive success (Frederick and Collopy 1989;Giese 1996;Smith 1998;Walker et al 2005;Mills et al 2008). Few studies have focused specifically on the effects of research activities on free-ranging mammals, although such activities may also impact behaviour or survival (Chapman 1977, Laurenson andCaro 1994;Wolski et al 2004;Frame et al 2007;Habib and Kumar 2007). These studies, and anecdotal evidence from other studies (e.g., Harrison and Gilbert 1985;Mowat et al 1996;Way et al 2001), suggest that mammals typically react adversely to disturbance at homesites on a short temporal scale that does generally not affect subsequent survival or reproduction.…”
Section: Introductionmentioning
confidence: 99%